2022
DOI: 10.3390/genes13060945
|View full text |Cite
|
Sign up to set email alerts
|

Association between SNPs in Leptin Pathway Genes and Anthropometric, Biochemical, and Dietary Markers Related to Obesity

Abstract: Obesity is one of the main public health problems in Mexico and the world and one from which a large number of pathologies derive. Single nucleotide polymorphisms (SNPs) of various genes have been studied and proven to contribute to the development of multiple diseases. SNPs of the leptin pathway have been associated with the control of hunger and energy expenditure as well as with obesity and type 2 diabetes mellitus. Therefore, the present work focused on determining the association between anthropometric ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…These results are consistent with other studies; for example, in the Chinese population, an allelic variant of PCSK1 rs6234 was associated with increased BMI and waist circumference [25,26], and, in the young European-American population, these SNPs were associated with increased BMI [27]. Similar results were found in British and Mexican subjects [28,29]. The increase in BMI, weight, waist circumference, and HR associated with the PCSK1 SNP in this population could be because this SNP is strongly associated with obesity due to alterations in thermogenesis and feeding, among other metabolic changes, increasing the anthropometric characteristics mentioned above [26].…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with other studies; for example, in the Chinese population, an allelic variant of PCSK1 rs6234 was associated with increased BMI and waist circumference [25,26], and, in the young European-American population, these SNPs were associated with increased BMI [27]. Similar results were found in British and Mexican subjects [28,29]. The increase in BMI, weight, waist circumference, and HR associated with the PCSK1 SNP in this population could be because this SNP is strongly associated with obesity due to alterations in thermogenesis and feeding, among other metabolic changes, increasing the anthropometric characteristics mentioned above [26].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, our study is the first to demonstrate that red meat intake and BMI status may modulate the relationships between LEPR rs7602 or LEPR rs1171278 and CRC survival. Although the mechanisms underlying the observed interactions are not yet fully understood, the positive associations among red meat intake, BMI, and LEP levels, as demonstrated in previous research 45,46 , may provide an explanation. In addition, we surmised that the influence of subtle differences among genotypes was overwhelmed by the detrimental effects of overweight/obesity or high red meat consumption on cancer outcomes.…”
Section: Table 3 Continuedmentioning
confidence: 64%
“…Several studies have reported complex genetic interactions between identified SNPs in metabolic diseases [35,36]. A recent study has used GWAS variant data to develop personalized organ-specific metabolic models for 524,615 individuals of the INTERVAL and UK Biobank cohorts to clarify the impact of genetic variations on the metabolic processes implicated in coronary artery disease [37].…”
Section: Discussionmentioning
confidence: 99%